Implementation of reading promotion and dissemination strategies from the Miriam Álvarez Brenes Children's Library (BIMAB) during the COVID-19 pandemic in the year 2021 - Víquez Gamboa, Cindy (2024)
The promotion and dissemination of reading from the space of the children’s library is a constant task that involves the implementation of a series strategies and dynamics, to strengthen and encourage different skills in the child that allow a better level of integral development. This article presents a methodology implemented by BIMAB, during the 2021 pandemic, for the development of educational activities. It should be noted that this methodology was implemented through the development of six formative activities with preschool children and teachers. One option to evaluate the planning is the implementation of a data collection tool that allows its continuous improvement.